The Study of Air Fuel Ratio for Open Furnace MILD Combustion of Biogas on Bluff-body Burner - M. M., Noor; Wandel, Andrew P.; Yusaf, Talal (2012)
Economical fuel cost is very critical in the heating industry. Lean combustion with high air fuel ratio (AFR) is normally practiced by the industry. Low air fuel ratio or rich combustion will result in unburned hydrocarbons (UHC). UHC is a waste and pollution to the environment. This paper discussed on the modelling of air fuel ratio for the moderate and intense low oxygen dilution (MILD) combustion of biogas on bluff-body burner. Biogas is a low calorific value (LCV) gas which was formulated by using 50% methane, 20% hydrogen and 30% carbon dioxide. AFR is the ratio of air and fuel injected to the combustion chamber. Nozzle outlet size for air and fuel plays important role to determine AFR. In this study, the air and fuel nozzle size ratio used is 23:1. The AFR will be evaluated based on the UHC produced by the combustion. Stoichiometric AFR occurred when zero UHC and zero excess oxygen flow through the EGR pipe. The result shows that when AFR is 4.0, zero UHC was detected in the EGR. UHC in EGR will be waste and create unwanted combustion at the wrong location.